Autism and autistic traits in those who died by suicide in England. (November 2022) - Cassidy, Sarah; Au-Yeung, Sheena; Robertson, Ashley; Cogger-Ward, Heather; Richards, Gareth; Allison, Carrie; Bradley, Louise; Kenny, Rebecca; O'Connor, Rory; Mosse, David; Rodgers, Jacqui; Baron-Cohen, Simon
Abstract : Background: Autism and autistic traits are risk factors for suicidal behaviour. Aims: To explore the prevalence of autism (diagnosed and undiagnosed) in those who died by suicide, and identify risk factors for suicide in this group. Method: Stage 1: 372 coroners' inquest records, covering the period 1 January 2014 to 31 December 2017 from two regions of England, were analysed for evidence that the person who died had diagnosed autism or undiagnosed possible autism (elevated autistic traits), and identified risk markers. Stage 2: 29 follow-up interviews with the next of kin of those who died gathered further evidence of autism and autistic traits using validated autism screening and diagnostic tools. Results: Stage 1: evidence of autism (10.8%) was significantly higher in those who died by suicide than the 1.1% prevalence expected in the UK general alive population (odds ratio (OR) = 11.08, 95% CI 3.92–31.31). Stage 2: 5 (17.2%) of the follow-up sample had evidence of autism identified from the coroners' records in stage 1. We identified evidence of undiagnosed possible autism in an additional 7 (24.1%) individuals, giving a total of 12 (41.4%); significantly higher than expected in the general alive population (1.1%) (OR = 19.76, 95% CI 2.36–165.84). Characteristics of those who died were largely similar regardless of evidence of autism, with groups experiencing a comparably high number of multiple risk markers before they died. Conclusions: Elevated autistic traits are significantly over-represented in those who die by suicide.